2021
DOI: 10.1111/aphw.12261
|View full text |Cite
|
Sign up to set email alerts
|

Stress, physical activity, and screen‐related sedentary behaviour within the first month of the COVID‐19 pandemic

Abstract: This study investigated how stress, physical activity and sedentary behaviours, of a small sample of Canadians, changed within the first month (i.e. March/April) of the COVID‐19 pandemic and the reasons/barriers associated with such changes. Individuals who regularly wear activity trackers were recruited via social media. Participants ( N = 121) completed fillable calendars (March/April 2020) with their step counts and answered an online survey. Separate paired‐sample t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 27 publications
(41 reference statements)
4
53
2
1
Order By: Relevance
“…The COVID-19 pandemic continues to impact the health of Canadian adults. Researchers of studies conducted during the same timeframe as the current study have found that the pandemic has influenced Canadians' physical activity both positively [10] and negatively [2,10,11] while their screen time [12] and sedentary behavior have increased [11]. Canadian adults also reported higher levels of distress and negative mental health as a result of the pandemic [11,13], as well as improvements in healthy food consumption [14] and increased junk food consumption [12] compared to pre-pandemic.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…The COVID-19 pandemic continues to impact the health of Canadian adults. Researchers of studies conducted during the same timeframe as the current study have found that the pandemic has influenced Canadians' physical activity both positively [10] and negatively [2,10,11] while their screen time [12] and sedentary behavior have increased [11]. Canadian adults also reported higher levels of distress and negative mental health as a result of the pandemic [11,13], as well as improvements in healthy food consumption [14] and increased junk food consumption [12] compared to pre-pandemic.…”
Section: Introductionmentioning
confidence: 54%
“…Researchers of studies conducted during the same timeframe as the current study have found that the pandemic has influenced Canadians' physical activity both positively [10] and negatively [2,10,11] while their screen time [12] and sedentary behavior have increased [11]. Canadian adults also reported higher levels of distress and negative mental health as a result of the pandemic [11,13], as well as improvements in healthy food consumption [14] and increased junk food consumption [12] compared to pre-pandemic. Specifically, Di Sebastiano and colleagues [2] conducted a 10-week nation-wide study to investigate changes in the physical activity levels of Canadian adults (n = 2338, 35-44 years) prior to and immediately following the introduction of physical distancing guidelines in Canada.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In [ 107 ], the authors analyzed the stress level of a small group of Canadians who wore activity trackers and tracked their stress level during the initial month of the COVID-19 pandemic. The findings of the study provided good results.…”
Section: Research Directions In Terms Of Wearables For the Covid-19 Pandemicmentioning
confidence: 99%